Robust DC microgrid operation with power routing capabilities - James Amankwah Adu (Energy Reports, 2022)
This paper proposes a robust DC microgrid (MG) operation scheme for intentional power routing (PR) within the MG or between the MG and the utility grid (UG). The MG consists of a photovoltaic (PV) system, a battery energy storage system (BESS), and AC loads connected to the UG via a DC/AC power conditioning system. The operation is achieved by controlling the UG converter and the converter of the BESS in the slack mode with the same or different terminal voltages. In this way, the bus voltage is regulated in a variable range while the magnitude and direction of power exchange between the UG and the MG are realized at the primary voltage control level. The procedure to select the voltage references of the terminals and the control schemes are presented. The system has been implemented in PSIM environment and simulation results proves the reliability and stability of the design.